PENGUATAN PENDIDIKAN SOSIAL KEAGAMAAN MELALUI KAJIAN FIQH AN-NISYA’ BAGI IBU-IBU PEMBINAAN KESEJAHTERAAN KELUARGA (PKK) DI DESA LARANGAN PERRENG PRAGAAN SUMENEP - Mohammad Firdaus (ABDINA: Jurnal Sosial dan Pengabdian kepada Masyarakat, 2023)
Community Empowerment Practices is a learning activity for students to get important lessons from the community. In this case, empowerment in Larangan Perreng Village is more focused on the socio-religious and education sector. The goal to be achieved in this activity is to create an "Activist Village in Religious Socialization". Students of the Dirosat Islamiyah Al-Amien Institute Prenduan are required to have special skills in the field of Islam which are very much needed by the community in spiritual development by not neglecting socio-cultural factors in accordance with the regional development program of the East Java region in general and the development of the district government. -districts on the island of Madura in particular. Meanwhile, the nature of the practice of community empowerment at the Dirosat Islamiyah Al-Amien Institute Prenduan is a process of transforming, inviting, independent, growing and educating the community so that they know their potential to be developed and identify existing problems, so that they can be handled independently by the community. society itself. Community empowerment is sought so that every individual can compete and have the opportunity to try to increase household income which will later affect community food security. This awareness and concern is also mentioned by Paulo Freire as conscientization as a form of critical awareness. Another great idea that also underlies the spirit of community service is the concept of organics intellectual by Antonio Gramsci. In simple terms, intellectual organics is not only concerned with scientific development an sich but also has concern and awareness of fighting and taking action to improve the human condition.